Sociabilidades e valores: um olhar sobre a família árabe muçulmana em São Paulo - Truzzi,Oswaldo (2008)
This study explores the sociability and family values of Muslim Arabs in São Paulo, Brazil, based primarily on 10 interviews with individuals of different age groups, socioeconomic strata, and genders. With Christian Arab families as the counterpoint, the article contextualizes the arrival of these immigrants and discusses and investigates the family dilemmas and practices permeated by a strong patriarchal trait and the challenges faced by this religious minority. The article concludes that the groups ethnicity and religiosity tend to be continuously reshaped as the group grows and reproduces in local society, reacts to the stereotypes attributed to it, and interacts more intensely with this same society through the new generations born in São Paulo.